Satisfaction as User Consumer of Services the Needs of Senior in Intention of Designers as well as Investor on Example of Project of Private Senior House in Ustroń - Fross, Klaudiusz (Acta Universitatis Lodziensis. Folia Oeconomica, 2013)
The final consumer of business principles of investor, and the design decisions always on end as final customer also. Then he be able to the best evaluate really or object fulfils his needs. However senior is specific customer, often about individual needs, expectations, opinions. Is fulfillment in one object these varied individual needs for tens persons possible? Or it is possible to guarantee the content conditions of residence as well as spending of time in "new house" the house of senior is what? It is one concrete example of commercial object was tried was how to show ex-ante evaluations they stood helpful in qualification of needs, expectations and standards. It was presented was way the thinkings with the help of investor as well as possibility of realization architectural methods. It problems were described was programmings and undertaking important financial decisions as well as functional-spatial.